(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
This paper aims to discuss how the theory of knowledge, mainly gnosiology and epistemology, can contribute to the study of the philosophical foundations of cognitive therapy. Furthermore, this study aims to analyze the influence of constructivism and critical rationalism in the development of therapeutic goals and techniques of cognitive therapy. These goals are achieved from reviewing the transcendental idealism of Kant, the concept of constructivism and the influence of cognitive psychology in cognitive therapy. It also examines the cognitive therapy as a scientific practice, based on the hypothetical-deductive method. In this direction, the steps of the therapeutic process in cognitive therapy and the application of some cognitive and behavioral techniques for each step are analyzed from the hypothetical-deductive method perspective, using research practices as an analogy. Finally, we discuss the vision of cognitive therapy as a learning process and the influence of the therapist in the therapeutic process